2007
DOI: 10.1016/j.neurobiolaging.2006.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Systemic hypoperfusion is associated with executive dysfunction in geriatric cardiac patients

Abstract: The present study examines the relationship between systemic hypoperfusion via cardiac output (CO) and neuropsychological performances emphasizing executive function in an aging cohort. Geriatric outpatients with treated, stable cardiovascular disease (CVD) and no history of neurological illness (n=72, ages 56-85) were administered cognitive measures with an emphasis on executive functioning. Echocardiogram findings were used to stratify participants into two groups: low CO (<4.0 L/min) and normal CO (> o r=4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
133
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 130 publications
(145 citation statements)
references
References 26 publications
(25 reference statements)
9
133
1
2
Order By: Relevance
“…Support is provided by a growing body of literature documenting that peripheral cardiovascular dysfunction is related to poor cerebrovascular health and diminished cognitive function in older patients with cardiovascular disease. [43][44][45][51][52][53][54][55] Due to the multifaceted nature of MetS, further research is necessary to explore the contributions of frank vascular disease to the observed cognitive taskϪrelated BOLD response changes in midlife. Further exploration of other potential mechanisms such as alterations in cerebral glucose metabolism and inflammation will also be valuable.…”
Section: Discussionmentioning
confidence: 99%
“…Support is provided by a growing body of literature documenting that peripheral cardiovascular dysfunction is related to poor cerebrovascular health and diminished cognitive function in older patients with cardiovascular disease. [43][44][45][51][52][53][54][55] Due to the multifaceted nature of MetS, further research is necessary to explore the contributions of frank vascular disease to the observed cognitive taskϪrelated BOLD response changes in midlife. Further exploration of other potential mechanisms such as alterations in cerebral glucose metabolism and inflammation will also be valuable.…”
Section: Discussionmentioning
confidence: 99%
“…Medial calcification deposits, elastic breakdown, collagen crosslinking, and intimal-medial thickening confer predominant vascular stiffening 46,15,43,44 , i.e., changes that can hinder the normal ventricular-vascular coupling dynamics and can contribute to progressive impedance and progressive potential for peripheral hypoperfusion 6 . Oxidative stress may compound propensity for endothelial-independent vascular abnormalities 45,46 . Accumulating free radicals with age and disease can interrupt normal smooth muscle vasodilatory mechanisms, i.e., diminishing vasodilatory responses to exogenous as well as endogenous nitrates.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that GLS would relate to cognition, especially memory13, 14 and executive function,15, 16 known to be most affected by compromised cardiovascular function. We also hypothesized that GLS would have stronger associations with cognition than LVEF.…”
mentioning
confidence: 99%